Case Study: LCA Methodology Applied to Materials Management in a Brazilian Residential Construction Site - João de Lassio; Josué França; Kárida Espirito Santo; Assed Haddad (Journal of Engineering)
The construction industry is increasingly concerned with improving the social, economic, and environmental indicators of sustainability. More than ever, the growing demand for construction materials reflects increased consumption of raw materials and energy, particularly during the phases of extraction, processing, and transportation of materials. This work aims to help decision-makers and to promote life cycle thinking in the construction industry. For this purpose, the life cycle assessment (LCA) methodology was chosen to analyze the environmental impacts of building materials used in the construction of a residence project in São Gonçalo, Rio de Janeiro, Brazil. The LCA methodology, based on ISO 14040 and ISO 14044 guidelines, is applied with available databases and the SimaPro program. As a result, this work shows that there is a substantial waste of nonrenewable energy, increasing global warming and harm to human health in this type of construction. This study also points out that, for this type of Brazilian construction, ceramic materials account for a high percentage of the mass of a total building and are thus responsible for the majority of environmental impacts.